Effects of Water and 50% Ethylene-Glycol Coolant Characteristics on Nucleate Boiling Heat Transfer in IC Engine Cooling System - Haoyu Chen; Takashi Suzuki; Koki Asano; Ryota Shindo; Ayumi Homma; Naoya Kimata; Takaki Nakaya; Kakeru Nakamura; Emir Yilmaz; Mitsuhisa Ichiyanagi (International Journal of Automotive Engineering, 2021)
To improve the cooling system of internal combustion engines, the utilization of the nucleate boiling heat transfer is desired. Our previous study revealed the relationship between the water nucleate boiling heat flux and dimensionless numbers. By using 50% ethylene glycol aqueous solution (EG50%) as coolant, the nucleate boiling heat flux was measured on the corroded heating surface and compared with the experimental data of water as coolant. Subsequently, dimensional analyses were done to investigate the necessary dimensionless numbers affecting the forced flow nucleate boiling. Two new models are proposed for water and EG50% as coolants, and predicted heat flux results were found to be in an average error of 9.7% and 10.1%, respectively.